Diaspora in two Caribbean Novels: Levy´s Small Island and Phillips´s A State of Independence - Bonnici, Thomas (Revista de Letras, 2007)
The novels Small Place by Andrea Levy and A State of Independence by Caryl Phillips, respectively published in 2004 and in 1986, are analyzed. Since both deal with the trasnational diaspora of Caribbeans migrating to Britain, postcolonial problems concerning home and identity in the colonial subjects are discussed and the processes involving the diasporic agente are problematized. Results show that the subjectivity of the colonial transmigrant is constructed either by interventions within racialized society or by disruptions against colony-minded native rulers sticking to the status quo.